2012
DOI: 10.1074/jbc.m112.395731
|View full text |Cite
|
Sign up to set email alerts
|

Light-dependent Structural Change of Chicken Retinal Cryptochrome4

Abstract: Background: Photoreaction and localization of vertebrate cryptochrome are not well understood. Results: We found that chicken cryptochrome4 is expressed in the retina. The carboxyl terminus of chick retinal cryptochrome4 bound with a specific antibody in a light-dependent manner. Conclusion: Molecular accessibility of the carboxyl-terminal region of chick retinal cryptochrome4 changes upon light illumination. Significance: Nonmammalian vertebrate cryptochromes are likely involved in light-dependent physiology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
81
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 24 publications
4
81
0
1
Order By: Relevance
“…In chickens, as in other birds, there are at least four types of cryptochrome (Bailey et al, 2002;Haque et al, 2002;Liedvogel and Mouritsen, 2010;Watari et al, 2012). Of these, cryptochrome 1a has been found to be located at the disks in the outer segments of the ultraviolet/violet cones of robins and chickens (Nießner et al, 2011), and thus at a location that is in agreement with a sensory function.…”
Section: Introductionmentioning
confidence: 58%
“…In chickens, as in other birds, there are at least four types of cryptochrome (Bailey et al, 2002;Haque et al, 2002;Liedvogel and Mouritsen, 2010;Watari et al, 2012). Of these, cryptochrome 1a has been found to be located at the disks in the outer segments of the ultraviolet/violet cones of robins and chickens (Nießner et al, 2011), and thus at a location that is in agreement with a sensory function.…”
Section: Introductionmentioning
confidence: 58%
“…This indicates that our antiserum against an epitope on the C-terminus does not label all Cry1a forms but only an activated form. A similar light-dependent conformational change in chicken cryptochrome 4 leads to recognition by a specific antibody which may hence be used as a conformational probe [14]. The same applies to our antiserum against the C-terminal of Cry1a.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast to Type 1 Crys whose conformational changes happen mainly at the C-terminus [27], our study (and that of Mitsui et al [20] with GgCry4) shows that the changes in tryptic digestion of ClCry4 are detected within the PHR domain (Fig5B). Another study with GgCry4 found that light exposure affects binding of an anti-Cry4 antibody directed against a C-terminal epitope [56]. Unfortunately, these methods used to probe conformation are crude and it is not possible to systematically compare light-induced conformational changes in Type 1 and Type 4 Crys.…”
Section: Discussionmentioning
confidence: 99%